1997
DOI: 10.1177/095207679701200306
|View full text |Cite
|
Sign up to set email alerts
|

Spain, its regions and the EU ‘LEADER’ initiative: some critical perspectives on its administration

Abstract: This paper examines the development of the EU's LEADER Initiative for integrated rural development. It is argued that the policy process, specific to the LEADER Initiative, has to be understood in terms of the development of a ‘policy community’ in Brussels and beyond, engaged in policy developments informed by a clear ‘integrationist’ philosophy. The paper goes on to examine the administrative arrangements created within Spain to implement the EU's LEADER Initiative for integrated rural development. The inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A detailed comparative study of the application of LEADER 1 in the two areas of La Loma (Jaen province) and the Alpujarras (Granada and Almeria provinces) demonstrated that the characteristics of the two areas at the time of implementation (including local political trajectories) fundamentally influenced the nature of the activities proposed (Barke and Newton, 1997a). Elsewhere, the inevitable involvement of several levels of administrative bureaucracy in Spain militated against the genuine achievement of bottom up, 'grass roots', rural development (Barke and Newton, 1997b). Furthermore, the processes by which local rural development groups emerged varied immensely, with many being little more than pre-existing interest groups and local elites (Barke and Newton, 1997c).…”
Section: Rural Tourism In Spain 145mentioning
confidence: 98%
“…A detailed comparative study of the application of LEADER 1 in the two areas of La Loma (Jaen province) and the Alpujarras (Granada and Almeria provinces) demonstrated that the characteristics of the two areas at the time of implementation (including local political trajectories) fundamentally influenced the nature of the activities proposed (Barke and Newton, 1997a). Elsewhere, the inevitable involvement of several levels of administrative bureaucracy in Spain militated against the genuine achievement of bottom up, 'grass roots', rural development (Barke and Newton, 1997b). Furthermore, the processes by which local rural development groups emerged varied immensely, with many being little more than pre-existing interest groups and local elites (Barke and Newton, 1997c).…”
Section: Rural Tourism In Spain 145mentioning
confidence: 98%